Travel as a risk factor for uncomplicated Plasmodium falciparum malaria in the highlands of western Kenya. - Shanks, G; Biomndo, K; Guyatt, H; Snow, R (2005)
In the 1980s, highland malaria returned to the tea estates of western Kenya after an absence of nearly a generation. In order to determine the importance of travel for the spread of malaria in this region, we prospectively collected blood films and travel, demographic and geographic information on well persons and outpatients on tea estates near the western rim of the Rift Valley. Risk factors for malaria asexual parasitaemia included: tribal/ethnic group, home province and home district malaria endemicity. Travel away from the Kericho tea estates within the previous two months showed an odds ratio (OR) for parasitaemia of 1.59 for well persons and 2.38 for outpatients. Sexual stages of malaria parasites (gametocytes) had an OR of 3.14 (well persons) and 2.22 (outpatients) for those who had travelled. Increased risk of malaria parasitaemia with travel was concentrated in children aged <5 years. An increase in population gametocytaemia is possibly due to increased chloroquine resistance and suppressed infections contracted outside of the tea estates.